Mengukuhkan Nilai Religiusitas Desa Wonodadi Kecamatan Plantungan Kabupaten Kendal Melalui Pembacaan Kitab Berzanji - Radipta Putra Pradana; Zulfatun Ni’mah Sabila; Syifa Lutfiatun Nisa; Ruhadi Ruhadi (Universitas Negeri Semarang, 2026)
The religiosity of rural communities in Indonesia is an important aspect of daily life that helps shape cultural and social identity. Wonodadi Village, located in Plantungan District, Kendal Regency, is one of the villages known for its rich traditions and strong religious values. In the midst of modernization and globalization, many local traditions are threatened with extinction. However, through the reading of Berzanji, the people of Wonodadi Village have succeeded in maintaining their cultural and religious heritage, making it an integral part of community identity. This paper aims to determine the implementation of the strengthening of religious values in Wonodadi Village through the reading of the Berzanji book. The method used is a community service program. Community service programs can be implemented through various methods involving training, mentoring, and guidance. The results of the service show that the congregation of the study group in Wonodadi Village routinely holds Berzanji activities every Monday afternoon to increase their love for the Prophet. They also read Sholawat as a form of respect for the Prophet Muhammad. This tradition aims to develop adolescent morals and da'wah values in the Berzanji culture to create tolerance in the village.